Occurrence and distribution of seagrasses in waters of Perhentian island archipelago, Malaysia - Zakaria @ Ya, Muta Harah; Bujang, Japar Sidik (Academic Journals, 2013)
The Perhentian Island archipelago, Terengganu in east coast of Peninsular Malaysia is relatively in isolation from the mainland and poor accessibility has led to the paucity of observation on marine animals and plants e.g., seagrasses for the archipelago. Field surveys on seagrasses around Perhentian Besar Island and Perhentian Kecil Island was conducted for occurrence and distribution of seagrasses. Plants were sampled by direct collection during low tide or by snorkelling and SCUBA diving over four years (2007-2010) as part of the inventory of marine plants. Five species of seagrasses comprising the rare larger-bodied, Enhalus acoroides (L.f.) Royle and the small-bodied Halophila decipiens Ostenfeld, H. minor (Zoll.) den Hartog, H. ovalis (R. Brown) Hooker and Halodule pinifolia (Miki) den Hartog were recorded around the two islands. Enhalus acoroides grew in isolated patches at shallow depths of 0.5-1.5 m of the littoral zone usually exposed during the low spring tides at Tanjung Batu Lepir. Halophila decipiens, H. minor, H. ovalis and Halodule pinifolia grew as monospecific or mixed populations with no distinct zonation distributed at deeper depths of 4.6-12.0 m of the sublittoral zones at Channel in front of Department of Fisheries, Channel in front of Coco Hut and Kg. Tanjung Aur. Seagrass characterized by small-bodied with flaccid leaves e.g., Halophila decipiens, H. minor, H. ovalis and Halodule pinifolia are uniquely equipped for survival under extreme physical oceanographic due to seasonal north-east monsoons prevailing at Perhentian islands, making them less vulnerable to wave action and become detached. The morphological descriptions of the five species are also described.